Answer:
yes
Step-by-step explanation:
x increases by 2, and y increases by 3 consistently
After putting the value of y from the second equation to the first equation, the resultant equation is
.
GIven:
The equations are:
![3x + y = 1\\ y = 6 - 4x](https://tex.z-dn.net/?f=3x%20%2B%20y%20%3D%201%5C%5C%0Ay%20%3D%206%20-%204x)
It is required to put the value of y from second equation to the first equation.
<h3>How to solve equations?</h3>
The value of y from the second equation is,
![ y = 6 - 4x](https://tex.z-dn.net/?f=%0Ay%20%3D%206%20-%204x)
Now, put this value of y in the first equation as,
![3x + y = 1\\ 3x+(6 - 4x)=1\\ 3x+6-4x=1\\ -x=-5\\ x=5](https://tex.z-dn.net/?f=3x%20%2B%20y%20%3D%201%5C%5C%0A3x%2B%286%20-%204x%29%3D1%5C%5C%0A3x%2B6-4x%3D1%5C%5C%0A-x%3D-5%5C%5C%0Ax%3D5)
Therefore, after putting the value of y from the second equation to the first equation, the resultant equation is
.
For more details about equations, refer to the link:
brainly.com/question/2263981
Answer: Our required probability is 0.39.
Step-by-step explanation:
Since we have given that
X be the exponentially distributed with mean life = 6 years
So, E[x]=6
![\dfrac{1}{\lambda}=6\\\\\lambda=\dfrac{1}{6}](https://tex.z-dn.net/?f=%5Cdfrac%7B1%7D%7B%5Clambda%7D%3D6%5C%5C%5C%5C%5Clambda%3D%5Cdfrac%7B1%7D%7B6%7D)
So, our cumulative distribution function would be
![F(x)=1-e^{-\lambda x}](https://tex.z-dn.net/?f=F%28x%29%3D1-e%5E%7B-%5Clambda%20x%7D)
We need to find the probability that the CPU fails within 3 years.
![P(X](https://tex.z-dn.net/?f=P%28X%3C3%29%3DF%283%29%3D1-e%5E%7B-%5Cfrac%7B1%7D%7B6%7D%5Ctimes%203%7D%5C%5C%5C%5C%3D1-e%5E%7B-%5Cfrac%7B1%7D%7B2%7D%7D%5C%5C%5C%5C%5Capprox%200.39)
Hence, our required probability is 0.39.
Answer: 98 degrees
Step-by-step explanation:
What kind of operation is this ? it just says x and a nine.